Potential of using Portulaca oleareca in the development of products for people with autism spectrum disorder- TEA (Research, Society and Development, 2020)
The present study has as its theme to analyze the capacity of formulating products based on Portulaca Oleracea. The objective was to evaluate the potential of using Portulaca oleracea in the development of products for people with Autistic Spectrum Disorder (ASD). For the selection of the samples, criteria were defined for articles indexed from 2013 to 2020, published in national and international journals, available in full in Portuguese and English. Data collection was performed in the electronic database: Scientific Electronic Librany Online (SciELO), Nation Library o Medicine (PubMED) and Google Scholar. The following descriptors were used to survey the research: "purslane"; "portulaca"; "autistic spectrum disorder". The search initially resulted in 12 articles, after adopting the inclusion and exclusion criteria, eight articles remained for analysis, interpretation and discussion. The potentiality of Portulaca oleracea was observed in the studies analyzed, with regard to the large presence of bioactive compounds. Thus, it was possible to conclude that Portulaca oleracea has components with a high antioxidant content, and an abundance of essential vitamins, proteins and minerals for the proper functioning of the body of people with ASD and contribute to its symptoms and treatment.